The Influence of Religiosity Level on the Popular Culture Lifestyle of Muslim Students of the Faculty of Engineering, Brawijaya University - Erlanda Devin Nurzaini; Fahrizal Eka Putra Sunaryo; Ichsan Candra Furqoni; Nadil Ulum Annafis; Arrafi Syafino (International Journal of Technology and Education Research, 2026)
This study aims to analyze the influence of religiosity levels on the popular culture lifestyle of Muslim students at the Faculty of Engineering, Brawijaya University. The study used a quantitative approach with a survey design of 100 students selected through a purposive sampling technique. Data were collected through a Likert-scale questionnaire with 13 statements for the religiosity variable and 10 statements for the popular culture lifestyle variable, and were strengthened by semi-structured interviews. Reliability tests produced Cronbach Alpha values ​​of 0.680 for the religiosity variable and 0.738 for the popular culture lifestyle variable. Data analysis used descriptive statistics, the Shapiro-Wilk normality test, and the Spearman correlation test. The results showed that there was no significant relationship between religiosity levels and popular culture lifestyle (rs = -0.0002, p = 0.999). A total of 65% of respondents were in the high religiosity category, while 74% of respondents were in the medium popular culture lifestyle category, indicating that the two variables operate in parallel and independently. These findings indicate that religiosity does not serve as an absolute barrier to popular culture, but rather as a selective guide that helps students evaluate popular cultural content based on Islamic values. Further research is recommended to integrate moderating variables such as digital media literacy and self-control to uncover the deeper mechanisms behind this coexistence phenomenon.